SmartSynth: synthesizing smartphone automation scripts from natural language - Le, Vu; Gulwani, Sumit; Su, Zhendong (MobiSys'13, 2013)
This paper presents SmartSynth, a novel end-to-end programming system for synthesizing smartphone automation scripts from natural language descriptions. Our approach is unique in two key aspects. First, it involves a carefully designed domain-specific language that incorporates standard constructs from smartphone programming platforms to balance its expressivity and the ability to synthesize scripts from natural language. Second, our synthesis algorithm integrates techniques from two research areas: (1) It infers the set of components and their partial dataflow relations from the natural language description using techniques from the Natural Language Processing community; and (2) It uses techniques from the Program Synthesis community to infer missing dataflow relations via type-based synthesis and constructs scripts in a process akin to reverse parsing. SmartSynth also performs conversational interactions with the user when multiple top-ranked scripts exist or it cannot map part of the description to any component. Evaluated on 50 tasks collected from smartphone help forums, our system produces the intended scripts in real time for over 90% of the 640 natural language descriptions obtained from a user study for those tasks. SmartSynth has also been adapted to TouchDevelop, an end user-targeted programming environment on mobile platforms, with very promising results (see http://www.cs.ucdavis.edu/ su/smartsynth.mp4 for a video demo). We believe that SmartSynth is a step toward fully personalized use of smartphones' increasingly rich functionalities.